Determination of Capital Structure with the Influence of Financial Characteristics and Tax Aspects - Wirianata, Henny; Viriany (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
This study was conducted to obtain empirical evidence on the influence of financial characteristics and tax aspects on capital structure. Data samples were taken from the non-cyclical consumer sector listed on IDX in 2020 to 2023 with purposive random sampling. The results showed that firm size, profitability, and interest coverage ratio significantly negatively affect DER. Liquidity, non-debt tax shield, and tax rate significantly positively affect DER. Meanwhile, tangibility, asset growth, sales growth, and debt tax shield do not significantly affect DER. The results also showed that tangibility, firm size, and liquidity significantly negatively affect DAR. A non-debt tax shield and tax rate significantly positively affect DAR. Meanwhile, asset growth, sales growth, profitability, interest coverage ratio, and debt tax shield do not significantly affect DAR. All independent variables significantly affect capital structure proxied by DER and DAR.